Flowering and fruiting behavior of velvet apple (Asian Journal of Medical and Biological Research, 2016)
The study was conducted at three upazilla of Patuakhali during the period from the 1st February, 2013 to the 31st July, 2013 to evaluate the flowering and fruiting behavior of velvet apple germplasm. Twelve velvet apple germplasm were selected from three locations (DD 01, DD 04, DD 06, and DD 09 from Dumki; DD 02, DD 05, DD 08 and DD 10 from Mirzaganj; DD 03, DD 07, DD 11 and DD 12 from Patuakhali sadar upazilla) by field survey. The age of plant varied from 10 to 25 years having satisfactory growth and good health. A lot of variations in different parameters were observed among the germplasm. Flowering season started from 22 February and continued up to 20 April. Percentage of fruit setting ranged from 65.15 % to 92.26 % in DD 07 and DD 01, respectively. Required time for fruit maturation ranged from 116 days (DD 01) to 129 days (DD 07). Single fruit weight varied from 198.10 g (DD 12) to 238.90 g (DD 01). The highest number of seeds (8) was found in DD 07 while DD 01 was seedless. The length and diameter of fruit ranged from 6.72 cm (DD 07) to 8.04 cm (DD 01) and 6.09 cm (DD 07) to 7.27 cm (DD 01), respectively. The maximum edible portion (87.33 %) was recorded in seedless germplasm DD 01, while it was the lowest (42.00 %) in DD 07.Asian J. Med. Biol. Res. December 2015, 1(3): 660-669